Moving Communities Toward Policy Change: APPEAL's 4-Prong Policy Change Model. Issue 5 (September 2013) - Tong, Elisa K.; Lew, Rod
Policy change is recognized for underlying much of the success of tobacco control. However, there is little evidence and attention on how Asian American and Native Hawaiian and Pacific Islander (AA and NHPI) communities may engage in policy change. Challenges for AA and NHPI communities include the racial/ethnic and geographic diversity, and tobacco data accurately representing the communities. Over the past decade, the Asian Pacific Partners for Empowerment, Advocacy and Leadership (APPEAL) has worked to develop and implement policy change for AA and NHPI communities. This article describes APPEAL's 4-prong policy change model, in the context of its overall strategic framework for policy change with communities that accounts for varying levels of readiness and leadership capacity, and targets four different levels of policy change (community, mainstream institution, legislative, and corporate). The health promotion implication of this framework for tobacco control policy engagement is for improving understanding of effective pathways to policy change, promoting innovative methods for policy analysis, and translating them into effective implementation and sustainability of policy initiatives. The APPEAL strategic framework can transcend into other communities and health topics that ultimately may contribute to the elimination of health disparities.